BETWEEN BRILLIANCE AND SIMPLIFICATION: EXPLORING THE NATURE OF PLAIN LANGUAGE IN PUBLIC DISCOURSE - Мудринич, Світлана; Маслова, Лариса; Лисенко, Олена (SWorldJournal, 2025)
The article provides a comprehensive analysis of the phenomenon of plain language in political discourse as an effective tool for influencing the mass audience. Plain language is viewed as a strategic choice of a politician aimed at ensuring clarity, for